The association of classification and final rank with the percentage race time spent in different terrains during the para cross-country skiing world championships - Severin, A. C.; Podolski, M.; Sandback, Ø.; Kocbach, J.; Baumgart, J. K. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Para cross-country (XC) skiers compete across several classes in three categories (sitting, standing or visually impaired). The classes are dependent on the skiers` physical impairment and are each assigned a time factor, as % of total race time (RT), to ensure fair competition. The sport is performed across different terrains (uphill, downhill, flat), but it remains unknown whether cer tain terrain types affect performance in the different classes disproportionally. Therefore, this study aimed to investigate if the % RT spent in each terrain differed between classes, and if it was associated with the athletes` final rank within categories. Forty Para XC skiers were tracked with 10-Hz GNSS sensors during all middle-distance (sitting:7.5km/10km; standing/visually impaired:10km/12.5km) and long-distance (sitting:15km/18km; standing/visu ally impaired:15km/20km) XC skiing races at the 2022 Para Cross-Country Skiing World Cham pionships. Linear mixed models were used to investigate the association of classification and final rank, with both the individual % distribution of RT across terrain and the % race time lost relative to the fastest measured race time in each terrain type within a race. No associations were found between classification (p > 0.99) or the final rank (p > 0.99) and both % RTs. Therefore, this study shows that all athletes within each category spent approxi mately the same % RT in each terrain regardless of final rank and the severity of individual ath letes` impairments, as indicated by class.Consequently, this indicates that the current time factor system, without consideration of terrain, allowed for fair competition during the analysed races.